Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.8 - Solving Equations by Factoring and Problem Solving - Vocabulary, Readiness & Video Check: 2

Answer

$y=\{ -5,-3 \}$

Work Step by Step

By the Zero-Product Property, $ab=0$ implies $a=0 \text{ OR } b=0$. Hence, the solution to the given equation, $ (y+5)(y+3)=0 $, is \begin{array}{} y+5=0 \\ y=0-5 \\ y=-5 ,\\\\\text{OR}\\\\ y+3=0 \\ y=0-3 \\ y=-3 .\end{array} Hence, $ y=\{ -5,-3 \} $.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.